The Impact of Integration Strategy on Supply Chain Resilience: A Quantitative Study of Automotive Industry Companies in Morocco - kamar Moukadem; Abdelilah Elkharraz (International Journal of Scientific Research and Innovative Studies, 2024)
Supply chain resilience has become a subject of growing interest for both academia and business, due to the multiplicity of disruptive events affecting global supply chains, which make them highly vulnerable. The literature highlights that integration plays a central role in strengthening supply chain resilience. However, few empirical studies have explored this relationship in the automotive sector. This study aims to analyze the impact of integration on supply chain resilience within this sector. A survey was conducted among companies operating in the Moroccan automotive industry, and the data were processed using exploratory and then confirmatory factor analyses, based on Structural Equation Modeling (SEM) under the PLS approach. The results confirm that integration represents a major strategic lever for strengthening the resilience of automotive supply chains. Keywords: Supply Chain Resilience, Integration, Automotive Industry, PLS-SEM. Received Date: February 26, 2024 Accepted Date: March 18, 2024 Published Date: April 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/466